1990
DOI: 10.1159/000226780
|View full text |Cite
|
Sign up to set email alerts
|

Combination Chemotherapy with Pirarubicin (THP), Cyclophosphamide, Vincristine, and Prednisolone (VEP-THP Therapy) in the Treatment of Non-Hodgkin’s Lymphoma

Abstract: Twenty-eight patients with non-Hodgkin’s lymphoma (NHL) were treated with a combination of (2XXX-R)-4′-o-tetrahydropyranyladriamycin (pirarubicin, THP), cyclophosphamide, vincristine, and prednisolone (VEP-THP therapy). Eleven (45.8%) of twenty-four evaluable patients achieved complete response (CR). CR rate (52.8%) was higher in the intermediate-grade histology group than in high- or low-grade group. Toxicity was generally acceptable although leukopenia less than 2,000/ul was observed in 17 (60.7%) of 28 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…To reduce the risk of cardiotoxicity, we employed THP-adriamycin (pirarubicin) instead of ADR. Pirarubicin is a derivative of ADR with reportedly less cardiotoxicity in adults [19][20][21][22][23][24]. Recently, we have reported that no significant cardiac dysfunction was detected in long-term survivors of children with acute lymphoblastic leukemia who received THP treatment [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the risk of cardiotoxicity, we employed THP-adriamycin (pirarubicin) instead of ADR. Pirarubicin is a derivative of ADR with reportedly less cardiotoxicity in adults [19][20][21][22][23][24]. Recently, we have reported that no significant cardiac dysfunction was detected in long-term survivors of children with acute lymphoblastic leukemia who received THP treatment [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…A few published studies, most of which focused on elderly patients, have evaluated the THP-COP regimen in NHL patients. The CR rate in these reports ranged from 30.2 to 72.1%, and the OS rate (5-year results in most studies) ranged from 30.3 to 59.2% [18][19][20][21]. Only one study reported an 8-year OS of 17.4% for elderly patients with aggressive lymphoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…Aoki et al showed that chemotherapy regimens containing THP are useful and safe for elderly patients with NHL and that THP Non-hematological toxicity Nausea/vomiting 2 (5.0) 1 (2.5) Stomatitis 2 (5.0) 2 (5.0) Diarrhea 0 0 Constipation 1 (2.5) 1 (2.5) Liver dysfunction 1 (2.5) 2 (5.0) Renal dysfunction 1 (2.5) 0 Hematuria 1 (2.5) 0 Arrythmia 1 (5.5) 0 Heart failure 1 0 Respiratory failure 0 1 (2.5) Neuropathy 1 (2.5) 2 (5.0) Infection 1 (2.5) 2 (5.0) showed better results than DOX (Aoki et al 1998). Few reports on the efficacy of THP for treating NHL in young patients are available (Niitsu and Umeda 1998;Takagi et al 1990). In the present study, efficacy and safety were prospectively compared between biweekly THP-COP and CHOP regimens in the treatment of aggressive NHL in patients less than 70 years of age.…”
Section: Discussionmentioning
confidence: 99%